1998
DOI: 10.1212/wnl.50.2.570
|View full text |Cite
|
Sign up to set email alerts
|

Interferon treatment for multiple sclerosis

Abstract: are constantly negative, and peripheral T CD4+ cells remain low (last determination, 173 cells/mm").Severe CNS HSV-1 infections have never been described in patients with idiopathic T CD4t lymphocytopenia, despite the relevant role played by cellular immunity against HSV-1. Interestingly, our patient presented a radiologic picture of diffuse leukoencephalomyelitis, which is a very unusual presentation of CNS HSV-1 infection, even in patients with AIDS.6 Although the detection of HSV by PCR in CSF without histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 0 publications
0
20
0
2
Order By: Relevance
“…However, they are often indicated in situations, such as chronic viral hepatitis, where subsequent hepatotoxicity could be attributed to the underlying disease itself.There have been four reports in the literature of liver failure in MS patients also taking an interferon -IFN-alpha-2a which was never licensed in MS [35], IFNB-1a(sc) [36,37] and IFNB-1a(im) [38]. Thirty serious cases of symptomatic liver dysfunction were reported in a review article from one of the pharmaceutical manufacturers of IFNB [37].…”
Section: The Interferons and Liver Injurymentioning
confidence: 99%
“…However, they are often indicated in situations, such as chronic viral hepatitis, where subsequent hepatotoxicity could be attributed to the underlying disease itself.There have been four reports in the literature of liver failure in MS patients also taking an interferon -IFN-alpha-2a which was never licensed in MS [35], IFNB-1a(sc) [36,37] and IFNB-1a(im) [38]. Thirty serious cases of symptomatic liver dysfunction were reported in a review article from one of the pharmaceutical manufacturers of IFNB [37].…”
Section: The Interferons and Liver Injurymentioning
confidence: 99%
“…The use of IFN-b in MS is associated with autoimmune hepatitis (Durelli et al, 1998;Pulicken et al, 2006;Grieco et al, 2007), hepatotoxicity (Tremlett et al, 2004) and fulminant liver failure (Yoshida et al, 2001) and can occur years into treatment (Grieco et al, 2007). The use of IFN-b for MS has not been associated with unmasking PBC or precipitating de novo antimitochondrial antibodies (the classic serologic marker of PBC).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with MS receiving IFN-β, if de novo elevation of aminotransferases is mild, IFN-β treatment is often continued, and elevated aminotransferases return to almost nor mal [4] . However, severe liver dysfunction does not resolve simply after stopping IFN-β, and prompt treatment is needed.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-β is associated with hepatotoxicity, although it rarely induces severe liver injury. It was reported that autoimmune hepatitis (AIH) occurs during IFN-β therapy for MS [3,4] , but only one report has described the occurrence of AIH after intravenous methylprednisolone pulse therapy for MS [5] . We describe herein a case of a MS patient who developed AIH after treatment with IFN-β and pulsed methylprednisolone.…”
Section: Introductionmentioning
confidence: 99%